Operating reach trucks safely (Platinum series, 2000)
This program discusses common hazards presented by the operation of reach trucks and how to control those hazards through safe operating techniques. Topics include reach truck stability and handling characteristics, pre-operational inspection, lifting and moving loads safely, avoiding tip-overs, and travelling on sloped surfaces. Safe driving techniques, preventing injuries to pedestrians, lifting personnel safely, parking the truck and working in and around trailers and railcars are other addressed issues.